Performance Analysis Of Passive AirCooling System Pvt Utilizing Phase Change Material - Atheer S. Hassoon; Ghaidaa M. Ahmed; Shaymaa A. Hameed (Global Scientific Publishing, 2025)
Phase Change Materials (Paraffin wax-RT42) were included into Photovoltaic Thermal (PVT) systems to examine their thermal performance and the generation of electricity. The experimental setup is made up of two polycrystalline (PVT) panels, each of which has a power rating of 10 watts and measures 360 millimeters by 240 millimeters by 5 millimeters. All of the experimental tests were carried out in the city of Babel for February and March 2024 months, which is located in Iraq, with passive cooling method
Keywords: Photovoltaic Thermal; PCM; Sustainability of Solar Energy